2015
DOI: 10.7897/2277-4572.04560
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Practices and Associated Factors Among Pregnant Women in Wondo Genet District, Southern Ethiopia: A Cross-Sectional Study

Abstract: Diet is one of the prime determinants of health and nutritional status. An inadequate diet, poor in both quality and quantity, is one of the major reasons for high levels of malnutrition in women. A cross-sectional survey was conducted to assess dietary practices and to identify factors associated with sub-optimal dietary practices of pregnant women in Wondo Genet District, Southern Ethiopiain. A two-stage cluster sampling technique was used to select a representative sample of 153 pregnant women aged 19-49 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 11 publications
7
20
2
Order By: Relevance
“…In this study, income was significantly associated with food taboo. Pregnant women who earned 650-1000 birr were 56% less likely to have food taboo compared to pregnant women who have <650-birr monthly income, which is in line with the study done in Wondo Genet [12], Bangladesh [13], and Ogan state of Nigeria [14]. As income increases, the avoidance of food taboos decreases.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, income was significantly associated with food taboo. Pregnant women who earned 650-1000 birr were 56% less likely to have food taboo compared to pregnant women who have <650-birr monthly income, which is in line with the study done in Wondo Genet [12], Bangladesh [13], and Ogan state of Nigeria [14]. As income increases, the avoidance of food taboos decreases.…”
Section: Discussionsupporting
confidence: 86%
“…Based on this study, banana has not been eaten by 107(35.7%) of pregnant women which is not comparable with the study conducted in Hydya Zone (8.6%). This discrepancy may be due to the study area, culture, and time difference [12].…”
Section: Discussionmentioning
confidence: 91%
“…On the other hand, study showed that good dietary practice was found to be low (40.1%) in Gondar during pregnancy (Mekonnen et al, 2015). In addition energy and most of the nutrients intakes of pregnant mother in Wando Genet district is also reported to be lower than recommended for pregnant mother (Kuche et al, 2015). The inadequate dietary pattern in our study is however by far very high compared to the above studies.…”
Section: Discussioncontrasting
confidence: 74%
“…This is because urban residents are tought to have better education, health information and access to health facilities for antenatal care which subsequently promotes birth weight (Kuche et al, 2015;Taddese et al, 2016). It was found that there is a positive association in multivariable linear regression analysis between (maternal MUAC, parity and wealth index) and birth weight after adjusting for dietary diversity score (DDS), age at first marriage and food insecurity.…”
Section: Discussionmentioning
confidence: 99%
“…While others restrict their food intake during pregnancy for different reasons such as have smaller fetuses because smaller fetuses will carry a lower risk of delivery complications. (Kuche, D., Singh, P& ,.Moges, D. (2015) In the mid-west state of Nigeria, specifically in some parts of Ishan, Afemai, and Isoko Divisions pregnant women avoid snails. Whereas pregnant women of the Asaba Division are neither allowed to eat eggs nor drink milk.…”
Section: Introductionmentioning
confidence: 99%